Effect of Intramuscular Injection of Vitamin D on 25-Hydroxyvitamin D Levels, Glycaemic Control, and Liver Enzymes in Libyan Patients with Type 2 Diabetes Mellitus - Alemam, Hafsa M.; ElJilani, Mouna M.; Bashein, Abdulla M. (Libyan International Medical University Journal, 2022)
Background Vitamin D is a fat-soluble hormone that plays an important role in glycaemic control. In addition, it has a positive effect on improving liver enzyme function.Aim This study was performed to examine the effect of intramuscular injection of vitamin D on serum 25-hydroxyvitamin D [25(OH)D] levels, glycemic control, and liver enzymes in Libyan patients suffering from type 2 diabetes mellitus (T2DM) with vitamin D deficiency.Methods and Materials This cross-sectional study enrolled 100 T2DM (50 males and 50 females). Their serum 25(OH)D, fasting blood glucose (FBG), and liver enzymes were measured at the baseline and 12 weeks after treatment with vitamin D (200,000 IU) injection monthly for 3 months. Data analysis involved the estimation of mean ± standard error (SE) and comparison of means between pre and post-treatment values using paired t-test. Independent t-test was used to compare the means between males and females. The level of significance was set at p < 0.05.Results Females had a lower 25(OH)D blood levels than males at baseline (7.03 ± 0.25 ng/mL versus 7.86 ± 0.26 ng/mL, respectively p < 0.02). 25(OH)D levels in both sexes was increased significantly from 7.45 ± 0.18 ng/mL to 26.69 ± 0.24 ng/mL after 12 weeks of vitamin D injections (p < 0.001), with no significant differences between male and females. FBG levels in both sexes was significantly decreased from 144.68 ± 1.84 mg/dL to 85.96 ± 0.34 mg/dL post treatment (p < 0.001). Alanine aminotransferase (ALT) was increased from 10.24 ± 0.17 U/L at baseline to 20.34 ± 1.15 U/L post treatment (p < 0.001). Similarly, aspartate aminotransferase (AST) was increased from 11.23 ± 0.21 to 20.57 ± 0.22 U/L (p < 0.001), and alkaline phosphatase (ALP) was decreased from 124.95 ± 1.15 U/L to 111.17 ± 1.27 U/L (p < 0.001). There were no significant differences between male and female liver enzymes either pre- or post-vitamin D injectionsConclusion Treatment with vitamin D injection showed a significant increase in 25(OH)D accompanied by decreased FBG and ALP levels and increased ALT and AST levels. Vitamin D levels should be monitored and adjusted in diabetic patients.
Keywords: 25(OH)D; ALP; FBG; AST; ALT; vitamin D; Libya